2009
DOI: 10.1111/j.1524-4725.2009.01319.x
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Weakness After Repeated Injection of Botulinum Toxin Type A Evaluated According to Bite Force Measurement of Human Masseter Muscle

Abstract: MBF was significantly lower after booster injection of BTX-A into the human masseter muscle, but it gradually recovered in a predictable pattern, and the degree of discomfort experienced by the subjects had little effect on normal mastication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 24 publications
2
35
0
1
Order By: Relevance
“…31 Therefore, only 25 U of BoNT-A was chosen for the present study. In addition, the reducing effect on the masticatory force was maximal at 4 weeks after BoNT-A injection, [31][32][33] and the maximum bite force gradually recovered within 12 weeks. So, we evaluated the effect of BoNT-A on RMMA episodes during sleep at the point when the maximum effect was exerted.…”
Section: Bont-a Injectionmentioning
confidence: 87%
See 1 more Smart Citation
“…31 Therefore, only 25 U of BoNT-A was chosen for the present study. In addition, the reducing effect on the masticatory force was maximal at 4 weeks after BoNT-A injection, [31][32][33] and the maximum bite force gradually recovered within 12 weeks. So, we evaluated the effect of BoNT-A on RMMA episodes during sleep at the point when the maximum effect was exerted.…”
Section: Bont-a Injectionmentioning
confidence: 87%
“…Masticatory muscle weakness can recover gradually from 4 to 12 weeks after BoNT injection in association with the changes of masticatory force. 32,33 In association with a decrease in the peak amplitude of EMG burst of RMMA episodes, the BoNT-A injection improved the subjective symptoms for morning jaw stiffness and tooth grinding during sleep. Morning jaw stiffness is commonly reported by the subjects with frequent RMMA episodes.…”
Section: Subjective Symptomsmentioning
confidence: 99%
“…Adverse event profiles associated with botulinum toxin treatment for masseter hypertrophy reportedly include swelling, bruising, injection site pain, headache, change in bite force, speech disturbance, muscle pain, facial asymmetry, xerostomia and prominent zygoma [18]. In our study, one patient complained of transient injection site pain after BTX-B injection.…”
Section: Discussionmentioning
confidence: 84%
“…10 More quantitative clinical studies have indicated that, at comparable time points, 60% to 80% of control force is still present. 31,32 Unlike our study, human bite force was measured with the subjects voluntarily clenching at a maximal force, a highly subjective procedure. This study, by isolating each masseter muscle, allowed a more reliable measure of muscular force production without the influence of other variables such as patient cooperation and of uninjected muscles of mastication such as the temporalis and medial pterygoid.…”
Section: Discussionmentioning
confidence: 98%